Pemodelan Dispersi Fosfat dan Evaluasi Strategi Mitigasi Pencemaran Limbah Deterjen Domestik di Saluran Irigasi Cibarani Menggunakan HEC-RAS - Ezzy Yuanita; Doddi Yudianto (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2026)
Phosphate pollution from domestic detergent wastewater poses a significant challenge to urban water quality, particularly in small drainage channels where detergent-derived sources and dispersion patterns have not been thoroughly investigated. This study focuses on the Cibarani Channel in Bandung, Indonesia, where phosphate primarily originates from household detergent discharge. The objective was to model the spatial–temporal dispersion of total phosphate (TP) and evaluate two control strategies: substitution with low-phosphate detergents and partial technical reduction of TP concentration. A steady-flow hydrodynamic and water quality model was developed using HEC-RAS by incorporating field data on flow discharge, TP, DO, BOD, and NH₃–N, as well as community survey results. Model performance was evaluated using R², RMSE, and Nash–Sutcliffe Efficiency (NSE). Simulations during wet and dry seasons showed that TP concentrations consistently exceeded the Class II water quality standard (0.2 mg/L), reaching peaks of 0.878 mg/L during the wet season and 0.578 mg/L during the dry season. The low-phosphate detergent scenario reduced TP concentrations by up to 58%, while the partial technical reduction scenario lowered concentrations close to the water quality standard even under low-flow conditions. Survey results indicated that all respondents were willing to adopt environmentally friendly detergents. The findings suggest that the combination of low-phosphate detergent use and partial technical TP reduction has the potential to become an effective management strategy for reducing phosphate pollution in urban drainage channels.